2017
DOI: 10.1038/s41388-017-0026-x
|View full text |Cite
|
Sign up to set email alerts
|

Histone methyltransferase KMT2D sustains prostate carcinogenesis and metastasis via epigenetically activating LIFR and KLF4

Abstract: Abnormalities in epigenetic modifiers are emerging as driving events in prostate cancer (PCa). The histone methyltransferase KMT2D, a frequently aberrant epigenetic modifier in various tumors, has an undefined role in PCa. Moreover, little is known regarding KMT2D’s mutation in Chinese patients or its downstream signaling pathways and targets. Here, we profiled the mutational spectrum of 32 significantly PCa-associated genes by using disease-targeted sequencing, and found that KMT2D was highly mutated (63.04%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 53 publications
6
84
0
Order By: Relevance
“…The present study adds to evidence supporting LIFR involvement in mediating resistance by demonstrating that overexpression of LIFR leads to STAT3 activation and confers resistance to T‐DM1 in HER2‐positive breast cancer cells. LIFR expression is regulated by many complex mechanisms, such as gene copy number changes, histone acetylation or methylation at the LIFR gene promoter, microRNA and so on . We found that the gene copy number of LIFR was not changed in BT‐474/KR cells (Figure ), and the exact mechanisms underlining LIFR overexpression in BT‐474/KR cells needed further research.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The present study adds to evidence supporting LIFR involvement in mediating resistance by demonstrating that overexpression of LIFR leads to STAT3 activation and confers resistance to T‐DM1 in HER2‐positive breast cancer cells. LIFR expression is regulated by many complex mechanisms, such as gene copy number changes, histone acetylation or methylation at the LIFR gene promoter, microRNA and so on . We found that the gene copy number of LIFR was not changed in BT‐474/KR cells (Figure ), and the exact mechanisms underlining LIFR overexpression in BT‐474/KR cells needed further research.…”
Section: Discussionmentioning
confidence: 86%
“…LIFR expression is regulated by many complex mechanisms, such as gene copy number changes, histone acetylation or methylation at the LIFR gene promoter, microRNA and so on. [31][32][33] We found that the gene copy number of LIFR was not changed in BT-474/KR cells ( Figure S1), and the exact mechanisms underlining LIFR overexpression in BT-474/KR cells needed further research.…”
Section: Stat3 Inhibition Overcomes T-dm1 Resistance In Vivomentioning
confidence: 95%
“…Hillman RT et al reported that inactivation resulted from truncating mutation of KMT2D gene tends to recurrence of adult‐type granulosa cell tumors of the ovary . Furthermore, Lv S et al detected anti‐metastasis outcome of prostate cancer cells after knockdown of MLL2 . Our data obviously showed that high expressed MLL2 TIL in invasive tumor front was vulnerable to 5‐year postoperative recurrence and metastasis for early‐stage OSCC patients.…”
Section: Discussionmentioning
confidence: 50%
“…A549 and H1299 cells were seeded in 15 mm confocal dish (3 × 10 4 cells/well) and allowed to grow overnight, and then cells were treated with vehicle or EVO (4, 8, and 16 μM for A549 cells and 1, 2, and 4 μM for H1299 cells, respectively) for 48 h. After harvested, cells were fixed in 4% cold paraformaldehyde, and then incubated with Notch3 primary antibody (1:1000, v/v) at 4°C overnight. After washing with PBS, cells were incubated with Alexa Fluor ® conjugated secondary antibodies (1:500, v/v) at room temperature for 1 h ( Lv et al, 2017 ). Images were captured using Leica TCS SP8 confocal microscope (Leica, GER).…”
Section: Methodsmentioning
confidence: 99%